Equidade de gênero e carreira: barreiras, facilitadores e conscientização de inequidades - Barros, Luana de Souza (2024)
Learning to recognize gender biases and their impacts can serve as support in women’s careers, as such knowledge allows to develop more promising ways to deal with stereotypes and gender discrimination in the workplace. Despite the importance of the theme, no validated instruments were found for the Brazilian context. This dissertation, therefore, has the general objective of adapting culturally and seeking evidence of validity of the KGE for the Brazilian context. The dissertation was divided into two studies. Study 1 was an integrative literature review in order to map barriers and supports of women’s careers to help in the adaptation process of the measure that evaluates perception of gender equity at work. Of the 34 studies analyzed, six barriers and four supports were found. Study 2 aimed to culturally adapt and seek evidence of validity of the KGE for the Brazilian context. After the adaptation process, 339 workers participated in the validation of the instrument, whose analysis indicated unidimensionality, reduction of three items of measurement, excellent adjustment indices and internal consistency, and the measure could be used in Brazil. The results of these studies can be used in proposals for professional development interventions for women, helping to reshape human resources practices and providing alternatives for women to recognize gender inequalities and act on them.